Epistemological Transformation and Subversive Agency: Negotiating Gender, Faith, and Culture among Contemporary Sundanese Women - Gina Giftia Azmiana Delilah; Nina Nurmila (HUMANISMA : Journal of Gender Studies, 2025)
This study examines the dynamics of gender relations among contemporary Sundanese women amid the intersecting influences of patriarchy, religion, and cultural modernity. It is grounded in the historical shift from egalitarian Sundanese values to a patriarchal system legitimized through religious interpretations. The study aims to identify women’s negotiation strategies and forms of agency in reinterpreting gendered power relations. Using a feminist qualitative approach informed by feminist epistemology, data were gathered through in-depth interviews with eleven Sundanese women aged 40–55 from diverse educational and professional backgrounds. The findings show that patriarchal ideology remains deeply rooted, particularly through norms such as ngawulaan salaki. Yet, women exercise subversive agency by negotiating equality in education, marriage, and domestic leadership. Education and reflective religiosity serve as key drivers of epistemological transformation, shifting their consciousness from obedience toward gender equality. Thus, gender transformation among Sundanese women emerges through an internal reinterpretation of religion and tradition rather than their rejection.